The effect of appropriate antibiotic use on the length of hospital stay in deep neck abscess (DNA) patients - Hesti Dyah Palupi; Dian Paramita Wulandari; Feri Trihandoko (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Deep neck abscess (DNA) is an emergency in the otorhinolaryngology head and neck surgery field due to the formation of abscesses in the potential space between the deep neck fasciae. It is typically caused by the expansion of infection from various sources, including the teeth, mouth, throat, paranasal sinuses, middle ear, and neck. The increase of DNA cases needs for improvement of patient management especially when the patients have comorbidities which lead to an extended length of treatment. The study aimed to evaluate the appropriateness of empirical antibiotics given according to culture results and any comorbid factors that affect the length of hospital stay (LOHS). It was case-control observational study involving 44 cases of DNA patients who treated at Dr. Sardjito General Hospital Yogyakarta in the period of January 2018 to December 2020. The patients were divided into two groups with 22 patients in each group. The first group was the DNA patients with > 7 d LOHS and the second one was those with ≤ 7 d.  No significantly relationship was observed between variables evaluated included the appropriate antibiotic use  (p=0.546). However, dental caries (DC) was significantly related with the LOHS (p=0.015). In conclusion, there is no relationship between the appropriate antibiotic use and the LOHS. However, the DC is risk factor that influence the LOHS in patients with DNA.